Who Produces Online Hate?: An Examination of the Effects of Self-Control, Social Structure, & Social Learning - Bernatzky, Colin (American journal of criminal justice, 2022)
The growing prevalence of hate material on the Internet has led to mounting concerns from scholars and policymakers alike. While recent scholarship has explored predictors of exposure, perception, and participation in online hate, few studies have empirically examined the social factors that lead individuals to produce cyberhate. Therefore, this work examines the production of online hate using online survey data (N = 520) of youth and young adults collected in December 2017. We draw on two commonly-cited criminological theories, the General Theory of Crime (GTC) and Social Structure-Social Learning Theory (SSSL), to understand social factors that contribute to producing cyberhate. In addition, we consider whether a broader relationship exists between the production of online hate and support for President Trump, whose rhetoric has gained traction among far-right and alt-right communities that traffic in hate. Logistic regression results show limited support for GTC, as low self-control is not a significant correlate of producing cyberhate after other relevant variables are considered. We find more robust support for SSSL, as the production of cyberhate is associated with an individual’s social location, online associations, and differential reinforcement. Moreover, we find evidence that individuals who approve of President Trump’s job performance are more likely to produce online hate.